Tendency and performance of the portfolio of investments of the Pension Funds: Case of the investments in the foreign - Palomino Selem, Carlos (2016)
This article, applying the micro attribution model, has like objective to analyze the performance of stock investment of the pension fund managers (AFP) to the called investment abroad. Many studies in Perú respect to AFP ‘s performance portfolios had been conducted using the framework of the efficient frontier. Other important aspect refers to the AFP’s make decision of choosing investors specialized to portfolio management directed outward; policy which failed to achieve profitability over of returns of market indices of regions where they traded at a later period to 2007-2008 financial crises.